SELF-TESTING AND INTEGRITY CONTROL OF INFORMATION RESOURCE CLIENT CODE - Самойленко, Денис Николаевич (Ukrainian Information Security Research Journal, 2015)
For the information protection from unauthorized accessit is necessary to realize methods of checking the authenticityof program from which the request has beenformed, especially in case of network communication.Existing methods allow authenticity checking of passiveobjects (text areas, images, etc) by digital watermarksintroduction. In the present work there are shown theseries of authenticity checking methods based on HTMLcode analysis. It was recommended using of distributedmethods of program code self-testing in a way close towatermarks. It was proposed a method of pseudopolymorphiccode forming by dynamic replacing of similarsemantic elements. The method were tested on severalpopular browsers, the same hash codes were obtained,there were shown some restrictions of usage. Realizationof proposed methods will increase the information securityof network resources.